(3GdMLL GdbhGWY aj eYQaI GdhGUd hGdbGWYs - (3CHh eMeO YHO Gddg Hf YHO GdQMef Hf CHj HcQ aVd GdMGL,J (B918 (3g` s ((3QVhGf Hf CMeO HGQVhGf s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ hHYO agPg fHPI aejG jJYjf eYQaJg ef UdI GdQMefhSejJg GdMLL GdbhGWY ai eYQaI GdhGUd hGdbGWY s
(3BNQgG (B:s
(3aEPG RddJ aGQLYhGPG ZVHJ aCeSc GfJgi hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B152 - (3U(B160s
(3bhHdJ Ydi GdCUd Gdefbhd efg MSH GdEecGfs
(3hYdjgG JbjjOGJs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs